التبرج في نظر الإسلام - Rosmawati Ismail; روسماواتي بنت إسماعيل (Universiti Sains Islam Malaysia, 2022)
Islam is a complete religion within the spheres. Islam emphasizes the beauty, soully and externally. External beauty gives focus on the beauty that can be seen, where as the beauty of the soul involves character, mannerism and wisdom of the beholder. Does modernization only give emphasis on external beauty and the beauty of the soul being neglected. Many believe that external beauty is the symbol of modernization, advancement and civilization. This research paper tries differentiate between the need to have external beauty and the need to develop the beauty of the soul from the Islamic perspective. The finding base on the Al-Quran and Al-Hadith, the opinions regarding this subject on the need to beautify the external possessions and the need to beautify the soul is discussed here.